2018
DOI: 10.1002/art.40573
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Drug‐Free Remission After Induction Therapy With Golimumab in Early Peripheral Spondyloarthritis

Abstract: Anti-TNF treatment in very early peripheral SpA results in a remarkably high rate of sustained clinical remission. More than 50% of patients continue to have remission of their disease after withdrawal of therapy, which highlights a defined window of opportunity permitting induction of drug-free remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…54 In contrast, the CRESPA trial showed that drug-free remission is an achievable target in early pSpA in at least 50% of patients. 55…”
Section: Treatmentmentioning
confidence: 99%
“…54 In contrast, the CRESPA trial showed that drug-free remission is an achievable target in early pSpA in at least 50% of patients. 55…”
Section: Treatmentmentioning
confidence: 99%
“…Over the past decades, there has been a general approach of early management in various immune-mediated inflammatory diseases (IMIDs). 34 37 This has been based on the hypothesis that early diagnosis and treatment may better control the underlying inflammatory character of the IMIDs and lead to favorable treatment outcomes, including functional impairment and structural damage. In AxSpA, there is a growing number of RCTs using TNF-α blockers, which show encouraging results in early disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Remission in Peripheral Spon dyloarthritis (CRESPA) study is a single center, double blind, placebo controlled trial of the TNFi golimumab in 60 patients with very early peripheral SpA (defined as a symptom duration of <12 weeks). The study design has been described previously (18,19). In order to investigate whether early treatment with TNFi would lead to subsequent drug free remission (the "window of opportunity" hypothesis), medication was withdrawn at the time point of sustained clinical remission, defined as the absence of clinical arthritis, enthesitis, and dactylitis at 2 major consecutive visits planned at weeks 12, 24, 36, and 48.…”
Section: Methodsmentioning
confidence: 99%